Hypomagnesemia because of nedaplatin for cervical cancer: A case report - Jun Komoda; Tetsuya Hori; Kotaro Sato; Kunio Kusajima; Taro Shimizu (Journal of General and Family Medicine, 2023)
Abstract A 76‐year‐old woman with cervical cancer was treated with nedaplatin, a platinum‐based drug. After the initiation of the treatment, she became aware of numbness, dizziness, and loss of appetite. Exploration of the causes revealed no clues, but blood tests revealed hypocalcemia and hypomagnesemia. She was treated with intravenous calcium and magnesium, which resolved calcium, magnesium levels, and her symptoms. She was diagnosed with hypomagnesemia because of nedaplatin. Regular follow‐up is necessary for patients during or after nedaplatin. Awareness of electrolyte disturbances may elucidate the accurate diagnosis even in patients with obscure symptoms, particular in undergoing or following anticancer therapies.